Olhares sobre currículo e práticas pedagógicas na escola da comunidade quilombola Pedra Branca: o ensinar e o aprender história e cultura afro-brasileira e africana - Sampaio, Michele de Oliveira (2019)
The research aimed to analyze the practices of quilombola school education, from the curriculum and pedagogical practicesin interface with the socio-cultural reality of the Quilombola Community PedraBranca, in Vargem Alta, Espírito Santo, Brazil. To support the study, we sought to support the theoretical contributions of Munanga (1996; 2009) and Oliveira (2011; 2016) to think about the concept of quilombo, as a political, social and cultural territory. Reflections on the concept of identity were supported by Hall's theory (2011; 2017). Considering the need to understand the curriculum conceptions, it was based on the theoretical contributions of Silva (2004), Sacristán (2000) and Gomes (2002; 2008; 2010; 2012; 2017); and to think about quilombola school education, the contributions of Miranda (2012; 2015), Arruti (2011) and Costa (2013). For this purpose, a qualitative research was developed, through an ethnographic case study, in a school located in a quilombola territory. Participating subjects were teachers, students, professionals from the school and the Municipal Secretariat of Education, as well as members of the quilombola community surveyed. The methodological instruments used were documentary consultation, semi-structured interview, participant observation and field diary, built from August to December 2018. For data analysis, content analysis was chosen. The research points to the need to establish a school curriculum that dialogues with the National Curriculum Guidelines for Quilombola School Education and the National Curriculum Guidelines for Ethnic Racial Relations Education and the Teaching of Afro-Brazilian and African History and Culture, Since the documents that directed the educational work of the researched school, such as the pedagogical political project and the curriculum, were based on the National Curriculum Guidelines for Rural Education. From these guidelines, it was intended to cover the universe of quilombola communities and the work with Law No. 10 639/03, in a complementary and interdisciplinary way. However, it was possible to observe that, through the relationships established between the subjects of daily school life and the community, another curriculum was formed, consisting of actions that dialogued with the history, memory, knowledge, and quilombola culture. From this perspective, the peasant curriculum began to be questioned, negotiated and resignified, considering the needs of the subjects and the community itself, as well as the knowledge and practices produced about African and Afro-Brazilian history and culture at school. Thus, the curriculum assumed different meanings and dialogued with the perspective of Quilombola School Education, influencing school practices in dialogue with the movements of relationships established in the quilombola territory. Therefore, the study points to evidence of an instituting movement of a quilombola school curriculum in an attempt to develop a democratic, multi-ethnic, intercultural and decolonizing education.